Does the "high sugar" trait of perennial ryegrass cultivars express under temperate climate conditions?. (28th January 2019) - Rivero, M. Jordana; Balocchi, Oscar A.; Moscoso, Cristian J.; Siebald, Juan Agustín; Neumann, Fabián Lukas; Meyer, Don; Lee, Michael R. F.
Abstract: The objective was to evaluate water‐soluble carbohydrate (WSC) and crude protein (CP) concentration of perennial ryegrass (PRG) cultivars with different genetic potential for producing WSC under two contrasting agronomic managements in temperate climate (southern Chile). A 4 × 2 factorial design was randomly allocated to 24 plots (31 m 2 each, three blocks): four PRG cultivars (diploid standard cultivar, "2nSt"; tetraploid standard cultivar, "4nSt"; diploid high sugar cultivar developed in New Zealand, "2nHSNZ"; and tetraploid high sugar cultivar developed in Europe, "4nHSEU") and two agronomic managements ("favourable, " defoliations at three leaves per tiller and nitrogen (N) fertilization rate of 83.3 kg N ha −1 year −1 ; "unfavourable, " defoliations at two leaves per tiller and N fertilization rate of 250 kg N ha −1 year −1 ). Herbage samples were collected in early spring, spring, summer and autumn. Concentration of WSC did not differ among cultivars in spring and summer, averaging 194 and 251 g/kg DM, respectively. The cultivar 4nHSEU had the greatest WSC concentration in early spring and autumn (187 and 266 g/kg DM, respectively) and the greatest CP concentration across samplings (average 230 g/kg DM). Favourable management improved WSC concentrations in early spring and summer and decreased CP in spring, summer and autumn. Annual DM yield did not vary with cultivar or management, averaging 8.43 t/ha. Within a 12‐month study at one site in a temperate environment in southern Chile, PRG cultivars have not shown a consistent expression of the "high sugar" trait, where a genetic × environment interaction might be operating.